Developing a Bogamon-Talk (board game of monopoly talking) to improve students' English speaking skills - Aminah, Siti; Shofiyuddin, Muh (Jurnal Inovasi Teknologi Pendidikan, 2025)
The rapid development of technology emphasizes the importance of effective learning media. Students often struggle with English speaking due to limited practice and monotonous learning methods. This study aims to develop BOGAMON-TALK (Board Game of Monopoly Talking) to enhance student motivation and speaking skills. Using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), this Research and Development (R&D) study involved 33 eighth-grade students from Darul Ulum Purwogondo Junior High School. Data collection used interviews and tests, and was analyzed quantitatively. Validation by material experts yielded a score of 4.6 (very feasible), while media experts rated it 4.0 (feasible). The product's effectiveness was shown by a significant increase in student performance: pretest (52.03) and posttest (88.03). These results suggest BOGAMON-TALK is both valid and effective in improving students’ English speaking skills. It is recommended that subsequent researchers consider the adaptation of this board-based educational game into non-print or electronic media to enhance its accessibility and facilitate the enhancement of English speaking skills.